# Physics 451 Homework Assignment #12 — Solutions Textbook problems: Ch. 8: 8.2.2, 8.2.5, 8.2.6, 8.2.10, 8.2.16 Chapter 8 8.2.

2 The Laplace transform of Bessel’s equation (n = 0) leads to (s2 + 1)f (s) + sf (s) = 0 Solve for f (s) This equation is amenable to separation of variables s df =− 2 ds f s +1 ⇒ ⇒ df s =− ds 2+1 f s ln f = − 1 ln(s2 + 1) + c 2

Fall 2004

Exponentiating this and redeﬁning the consant, we obtain f (x) = √ C s2 + 1

8.2.5 A boat, coasting through the water, experiences a resisting force proportional to v n , v being the instantaneous velocity of the boat. Newton’s second law leads to m dv = −kv n dt

With v(t = 0) = v0 , x(t = 0) = 0, integrate to ﬁnd v as a function of time and then the distance. This equation is separable k dv = − dt n v m For n = 1, this may be integrated to give
v v0

dv k =− n v m

t

dt
0

⇒ ⇒

1 n−1

1 v n−1

1
n−1 v0

=−

k t m
−1/(n−1)

(1)

v(t) =

(n − 1)k −(n−1) v0 + t m

This may be integrated once more to obtain x as a function of t
t t

x(t) =
0

v(t )dt =
0

−(n−1) v0

(n − 1)k + t m

−1/(n−1)

dt

Although this may look somewhat scary, it is in fact trivial to integrate, as it is essentially t (plus a constant) to some fractional power. The only diﬃculty is bookkeeping the various constants. For n = 2, the result is 1 m x(t) = 1 − 1/(n − 1) (n − 1)k = m (n − 2)k v0
−(n−1) −(n−1) v0

(n − 1)k + t m
(n−2)/(n−1)

1−1/(n−1) t

0

(2)

+

(n − 1)k t m

− v0

−(n−2)

If desired, the position and velocity, (2) and (1) may be rewritten as m x(t) = n−2 (n − 2)kv0 v(t) = v0
n−1 (n − 1)kv0 1+ t m −1/(n−1) (n−2)/(n−1)

−1

n−1 (n − 1)kv0 t 1+ m

As a result, it is possible to eliminate t and obtain the velocity as a function of position −1/(n−2) n−2 (n − 2)kv0 x v = v0 1 + (3) m Note that we may deﬁne xk = m n−2 (n − 2)kv0

which represents a length scale related to the resisting force and initial velocity. In terms of xk , the velocity and position relation may be given as v = v0 1+ x xk
−1/(n−2)

or

v0 v

n−2

=1+

x xk

Note that, in fact, it is possible to obtain (3) directly from Newton’s second law by rewriting it as dv k k = − v dt = − dx v n−1 m m and then integrating
v v0

dv v
n−1

=−

k m

x

dx
0

⇒ ⇒

1 n−2
n−2

1 v n−2 =1+

1
n−2 v0

=−

k x m

v0 v

n−2 (n − 2)kv0 x m

So far, what we have done does not apply to the special cases n = 1 or n = 2. For n = 1, we have k dv = − dt v m ⇒ ln v v0 =− k t m ⇒ v(t) = v0 e−(k/m)t

Integrating once more yields x(t) = mv0 (1 − e−(k/m)t ) k ⇒ v kx =1− v0 mv0

which is in fact consistent with setting n = 1 in (3). For n = 2, we have k dv = − dt 2 v m ⇒ 1 1 k − + =− t v v0 m ⇒ v(t) = v0 1 + (kv0 /m)t

Integrating this for position yields x(t) = kv0 m ln 1 + t k m ⇒ kx v0 = ln m v

8.2.6 In the ﬁrst-order diﬀerential equation dy/dx = f (x, y) the function f (x, y) is a function of the ratio y/x: dy y =g dx x Show that the substitution of u = y/x leads to a separable equation in u and x. If we let u = y/x, this means that y = xu. So, by the product rule du dy =x +u dx dx The above diﬀerential equation now becomes x du + u(x) = g(u) dx ⇒ du dx = g(u) − u x

which is separated in u and x. 8.2.10 A certain diﬀerential equation has the form f (x)dx + g(x)h(y)dy = 0 with none of the functions f (x), g(x), h(y) identically zero. Show that a necessary and suﬃcient condition for this equation to be exact is that g(x) = const.

The check for exactness is ∂ ∂ f (x) = (g(x)h(y)) ∂y ∂x or 0= dg(x) h(y) dx

Since h(y) is not identically zero, we may divide out by h(y) (at least in any domain away from isolated zeros of h), leading to dg(x)/dx = 0, which indicates that g(x) must be constant. 8.2.16 Bernoulli’s equation dy + f (x)y = g(x)y n dx is nonlinear for n = 0 or 1. Show that the substitution u = y 1−n reduces Bernoulli’s equation to a linear equation. For n = 1, the substitution u = y 1−n is equivalent to y = u1/(1−n) . Thus 1 1 dy du du = u1/(1−n)−1 = un/(1−n) dx 1−n dx 1−n dx Bernoulli’s equation then becomes 1 du un/(1−n) + f (x)u1/(1−n) = g(x)un/(1−n) 1−n dx Multiplying by u−n/(1−n) gives 1 du + f (x)u = g(x) 1 − n dx or du + (1 − n)f (x)u = (1 − n)g(x) dx

Sign up to vote on this title